2017
DOI: 10.1016/j.lwt.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical/microbial properties and life cycle assessment (LCA) of PLA-based nanocomposite active packaging

Abstract: 21To attend the growing consumer demand for novel ready-to-eat fresh cut fruits packaging polylactic acid 22 (PLA)-based active packaging was realized. The aim of these packaging is to provide an improved 23 protection and even to extend their shelf-life. PLA-based active packaging was prepared by adding 24 nanoclays and surfactants in its formulation. The evaluation of PLA-nanocomposite packaging was done 25 in comparison to pristine PLA and conventional plastic (polyethylene terephthalate, PET) using fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…In recent years considerable progress has been made in the field of bioplastics in terms of cost-reduction, efficiency, and antimicrobial properties and therefore some bioplastics are already in use. However, some mechanisms remain unknown and so further research in this field Extension of shelf life, improvement due to combination, increase of respiration rate, prevention of whitening of the carrots' surface, maintenance of firmness [50] Freshly cut melon Packaging based on PLA enriched with nanoclays and surfactants Improvement of the performance of the original PLA based material (without nanoclays), effective against microbial growth, eco-friendly production and low impact on human health, decrease of food loss due to extended shelf life [40] Barberries LDPE packaging container enriched with silver nanoparticles Improvement of sensory, physicochemical and physiological properties compared to conventional PE containers [59] High and low protein food EVOH with incorporated silver nanoparticles (0.1, 1 and 10 wt% silver)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years considerable progress has been made in the field of bioplastics in terms of cost-reduction, efficiency, and antimicrobial properties and therefore some bioplastics are already in use. However, some mechanisms remain unknown and so further research in this field Extension of shelf life, improvement due to combination, increase of respiration rate, prevention of whitening of the carrots' surface, maintenance of firmness [50] Freshly cut melon Packaging based on PLA enriched with nanoclays and surfactants Improvement of the performance of the original PLA based material (without nanoclays), effective against microbial growth, eco-friendly production and low impact on human health, decrease of food loss due to extended shelf life [40] Barberries LDPE packaging container enriched with silver nanoparticles Improvement of sensory, physicochemical and physiological properties compared to conventional PE containers [59] High and low protein food EVOH with incorporated silver nanoparticles (0.1, 1 and 10 wt% silver)…”
Section: Discussionmentioning
confidence: 99%
“…It is used for packaging materials for short shelf life products such as fresh RTE food, for example fruit and salads [40,41]. Current sources of the lactic acid needed to produce PLA for packaging films include for example corn, wheat, and sugar cane.…”
Section: Biodegradable Bioplastics (Pla) From Seaweedmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of writing (in 2016) though, nanocomposites can be said to hold great promise in flexible packaging, in the years to come, with optimisation likely to bring down the cost and thereby make the nanocomposites competitive with the alternatives. Lorite et al (2017) have shown that polylactic-acid-based nanocomposite active packaging, vis-à-vis polyethylene terephthalate (PET), can extend the shelf life of the food product, thus reducing food wastage, while being environmentally as good a performer as PET.…”
Section: Literature Reviewmentioning
confidence: 99%